Integrity pacts - Arribas Reyes, Esteban (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
This work analyses integrity pacts as a concept under construction –there is no scientific work on the particular– within the conceptual and theoretical logic of collective action and, in particular, on the application of these to the management of integrity of public procurement processes (transparency, accountability). Integrity pacts are born from the need to offer innovative anti-corruption solutions in the field of public procurement.